Delta opioid modulation of hypothalamic serotonergic neurotransmission in the ovariectomized and steroid-primed rat - Yilmaz, Bayram; Gilmore, Desmond P. (Maghira and Maas Publications, 2000)
OBJECTIVES: We have investigated the modulating effects of DPDPE (a ? opioid agonist) and opioid receptor antagonists on both LH release and indoleamine concentrations in specific hypothalamic regions of the ovx and steroid-primed rat. METHODS: DPDPE was intracerebroventricularly infused alone or with either ICI 154129 (a ? opioid antagonist) or naloxone under ketamine anesthesia. Blood samples were collected at hourly intervals on the afternoon of the anticipated LH surge. The rats were then decapitated and the medial preoptic area (MPOA), suprachiasmatic nucleus (SCN), median eminence (ME) and arcuate nucleus (ARN) surgically isolated by micropunch. Concentrations of 5-HT and its metabolite (5-HIAA) in these samples were determined by HPLC with ECD. Plasma LH levels were measured by RIA. RESULTS: The ?-agonist significantly reduced 5-HT concentrations in the SCN, ME and ARN, but not in the MPOA. 5-HIAA levels were decreased, but these changes were significant in only the MPOA and ARN compared to the control group. ICI 154129 had no significant effects on 5-HT release and turnover in any of the hypothalamic regions examined. However, co-administration of DPDPE with naloxone resulted in significant increases in 5-HT and 5-HIAA concentrations in the MPOA, SCN, ME and ARN compared to the DPDPE-treated group. Plasma LH levels were either low or undetectable in all groups. CONCLUSIONS: The present results suggest that ?-opioid receptors are involved in the opioid inhibition of the serotonergic neurotransmission in the hypothalamus. It is thought that the ketamine anesthesia interfered with LH secretory systems.
Keywords: Delta opioid receptors; HPLC-ECD; Ketamine; LH; Serotonin